2002
DOI: 10.1103/physrevlett.89.217601
|View full text |Cite
|
Sign up to set email alerts
|

Giant Dielectric Permittivity Observed in Li and Ti Doped NiO

Abstract: A giant low-frequency dielectric constant ( epsilon 0 approximately 10(5)) near room temperature was observed in Li,Ti co-doped NiO ceramics. Unlike currently best-known high epsilon 0 ferroelectric-related materials, the doped oxide is a nonperovskite, lead-free, and nonferroelectric material. It is suggested that the giant dielectric constant response of the doped NiO could be enhanced by a grain boundary-layer mechanism as found in boundary-layer capacitors. In addition, there is about a one-hundred-fold dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
373
4
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 669 publications
(448 citation statements)
references
References 17 publications
35
373
4
7
Order By: Relevance
“…Ever since, these material suffers multiple valance (Fe 3þ /Fe 2þ , Ti 4þ /Ti 3þ , Mn 3þ /Mn 4þ ) which can be correlated with oxygen vacancies is a common feature for the CDC effect in transition metal ions. [5][6][7][8][9][10][11] Worthwhile, LaFeO 3 ceramic also exhibit CDC up to 380 K. For the first time, Idress et al 12 reported a giant dielectric constant behavior in LaFeO 3 , which was an extrinsic effect due to Maxwell-Wagner relaxation. 11,12 Despite, it has few limitations, such as high leakage current, intrinsic antiferromagnetic and weak ME coupling at RT, which can hamper the large scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since, these material suffers multiple valance (Fe 3þ /Fe 2þ , Ti 4þ /Ti 3þ , Mn 3þ /Mn 4þ ) which can be correlated with oxygen vacancies is a common feature for the CDC effect in transition metal ions. [5][6][7][8][9][10][11] Worthwhile, LaFeO 3 ceramic also exhibit CDC up to 380 K. For the first time, Idress et al 12 reported a giant dielectric constant behavior in LaFeO 3 , which was an extrinsic effect due to Maxwell-Wagner relaxation. 11,12 Despite, it has few limitations, such as high leakage current, intrinsic antiferromagnetic and weak ME coupling at RT, which can hamper the large scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results suggest that the photo-induced effect in SrTiO 3 is consistent with the conductive-region model. Giant dielectric response in nonferroelectric materials has been reported for grains surrounded by the insulating grain boundary and is explained by the Maxwell-Wagner model, namely the conductive-region model (Homes et al, 2001;Wu et al, 2002;Dwivedi et al, 2010). SrTiO 3 crystal is a stoichiometric material and has no grain structure.…”
Section: Transient Birefringence In the Millisecond Regionmentioning
confidence: 99%
“…We will list here some of them: Li and Ti substituted NiO (Ref. 23 Fig. 8, the qualitative features of these materials are all the same: -a huge (" > 10 4 Þ and temperature stable dielectric permittivity in the high temperature range (T > 300 K), -a sharp decrease of this dielectric permittivity on cooling to temperatures lower than 300 K, the falling temperature decreasing on decreasing the operating frequency, -a related maximum of the imaginary part " 00 of the dielectric permittivity shifting versus frequency just like the " 0 step.…”
Section: Macroscopic Space Charges In Other Oxidesmentioning
confidence: 99%